Effect of Ball Feeling Training on Dribbling Skills of Nusantara FC Semarang Futsal Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of ball feeling training on the dribbling skills of futsal athletes at Nusantara FC Semarang. This study was motivated by the lack of dribbling skills among players and the limited variety of training exercises for basic dribbling techniques. This study used a quantitative method with a one-group pretest-posttest design, involving 20 futsal athletes aged 16-19 years from Nusantara FC Semarang. The data collection instrument used was a dribbling test based on Dewi & Pakpahan (2018), conducted before and after the ball feeling training intervention over 4 weeks. Data analysis techniques included a prerequisite test (normality test) and a paired sample t-test at a significance level of 0.05. The results of the study showed that ball feeling training had a significant effect on improving dribbling ability, with the average time decreasing from 15.24 seconds (pretest) to 12.75 seconds (posttest), and a significance value of 0.001 (p < 0.05). The conclusion of this study is that ball feeling training can effectively improve dribbling skills.